Production and disposition of purebred Jersey populations - Szendrei, Zoltán; Béri, Béla (Acta Agraria Debreceniensis, 2008)
In Hungary crossbreeding wit Jersey has been in practice since 2004. Uniquely in the Hungarian history of the Jersey breed two times fifty head pregnant heifers were imported in 2006. The aim of our study is to present through the description of the production and the type traits of the population the inherent possibilities of Jersey. The breed is presented by the figures of the rolling lactations, 305 day milk production, correlations between the traits and by the results of the evaluation of type traits. Analyses of the data were done by using independent samples t-test.Based on data of 87 cows the average number of days in milk  is 308 and 48 cows has finished lactation. During the rolling lactation they produced 5050 kg milk with 5.34% fat and 3.8% protein content.The first lactation Jersey cows’ production when corrected to 305 days was 5089 kg milk with 5.35% fat and 3.81% protein. Between the herds there was significant difference in milk kg, amount of fat produced, protein content and amount of protein produced. On the two farms distribution of cows belonging to different production levels is very different. The biggest difference is when categorized by the amount of milk produced.Correlation between the milk kg and fat kg is the greatest (r=0.950). Similar values were obtained for the correlation between fat and protein kg (r=0.919) and for the milk kg and fat kg (r=0,898). Disposition of the Jersey cows is very well balanced. Their stature, strength, body depth, dairy form, rump angle and pin width is favorable, the average scores are between 4.5 and 6.5. The leg of the cows is a bit sickly, and is hocking in a little with medium-low angled hoof. Average values of all traits describing the udder are between 4 and 5. Cows belonging to the two herds differ by disposition. Significant difference exists in the following traits: body depth, dairy form, pin width, rear leg - side view, rear leg, rear view, foot angle, fore udder attachment, teat length. TheJersey population imported to Hungary has a final score of 78 points which equals with the “good” qualification.